A rare case of Rosai-Dorfman disease mimicking a malignant lymphoproliferative process and IgG4-related disease - Czerwiński, Jakub; Pysiewicz, Mateusz; Sołek, Julia Maria; Opinc, Aleksandra; Robak, Tadeusz; Makowska, Joanna; Braun, Marcin (Contemporary Oncology/Współczesna Onkologia, 2025)
Rosai-Dorfman disease (RDD), or sinus histiocytosis with massive lymphadenopathy, is a rare histiocytic disorder that often mimics malignancies and immune-mediated conditions such as IgG4-related disease (IgG4-RD). We report a 73-year-old male with a 2-year history of systemic symptoms, including fever, significant weight loss, and generalised lymphadenopathy, accompanied by strikingly elevated IgG4 levels. Advanced imaging revealed metabolically active lesions in lymph nodes, paranasal sinuses, and bones, complicating the differential diagnosis and raising concerns for malignancy or IgG4-RD. Histopathological examination revealed hallmark features of RDD, including S-100 positivity highlighting emperipolesis and negative CD1a staining, leading to the final diagnosis. The patient initially improved with glucocorticosteroids but achieved sustained symptom resolution with methotrexate, underscoring the potential of antimetabolites for systemic RDD. This case exemplifies the diagnostic and therapeutic challenges of RDD, emphasizing the importance of a multidisciplinary approach and further investigation of targeted therapies for complex and systemic presentations.